Study of Batik Wastewater Treatment Using PAC (Poly Aluminum Chloride) as Coagulant and Organoclay (Montmorillonite-polydadmac) as Floccullant to Reduce Total Suspended Solid (TSS) and Total Dissolved Solid (TDS) - Sari, Novita Chandra; Nugraha, Irwan (Proceeding International Conference on Science and Engineering, 2017)
Batik wastewater treatment using PAC (Poly Aluminium Chloride) as a coagulant and organoclay (montmorillonite- polyDADMAC) as flocculants was investigated in this study. The purpose of this study was to analyze the quality of batik wastewater effluent before and after coagulation-flocculation and analyze the effectiveness of organoclay as flocculants of batik wastewater. Organoclay (montmorillonite-polyDADMAC) synthesised by reacting natural bentonite with polyDADMAC 0.4%. Coagulation and flocculation used jar test method with a speed stirring at 120 rpm for 2 minutes and slow stirring at 40 rpm with a variety of types, masses of flocculants and flocculation time. At first, batik wastewater had high levels of TSS and TDS levels. TSS and TDS levels reduced after coagulation-flocculation. Effectiveness of maximum TSS reduced at 99,74% with the addition of organoclay flocculant 2.5 g/L and flocculation time for 80 minutes. Effectiveness of maximum TDS reduced at 93,57% with the addition of organoclay flocculant 2.5 g/L and 60 minutes flocculation.